Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2015)
Overall in 2014, adding nitrogen (N) improved average wheat yields, but different N placement methods resulted in similar yields. Double-crop soybean yields were unaffected by tillage or the residual from N treatments that were applied to the previous wheat crop.
Keywords: tillage; nitrogen; placement; rotation